A review of total & added sugar intakes and dietary sources in Europe. Issue 1 (December 2017) - Azaïs-Braesco, Véronique; Sluik, Diewertje; Maillot, Matthieu; Kok, Frans; Moreno, Luis
Abstract Public health policies, including in Europe, are considering measures and recommendations to limit the intake of added or free sugars. For such policies to be efficient and monitored, a precise knowledge of the current situation regarding sugar intake in Europe is needed. This review summarizes published or re-analyzed data from 11 representative surveys in Belgium, France, Denmark, Hungary, Ireland, Italy, Norway, The Netherlands, Spain and the UK. Relative intakes were higher in children than in adults: total sugars ranged between 15 and 21% of energy intake in adults and between 16 and 26% in children. Added sugars (or non-milk extrinsic sugars (NMES), in the UK) contributed 7 to 11% of total energy intake in adults and represented a higher proportion of children's energy intake (11 to 17%). Educational level did not significantly affect intakes of total or added sugars in France and the Netherlands. Sweet products (e.g. confectionery, chocolates, cakes and biscuits, sugar, and jam) were major contributors to total sugars intake in all countries, genders and age groups, followed by fruits, beverages and dairy products. Fruits contributed more and beverages contributed less to adults' total sugars intakes than to children's. Added sugars were provided mostly by sweet products (36 to 61% in adults and 40 to 50% in children), followed by beverages (12 to 31% in adults and 20 to 34% in children, fruit juices excluded), then by dairy products (4 to 15% in adults and 6 to 18% in children). Caution is needed, however, as survey methodologies differ on important items such as dietary data collection, food composition tables or estimation of added sugars. Cross-country comparisons are thus not meaningful and overall information might thus not be robust enough to provide a solid basis for implementation of policy measures. Data nevertheless confirm that intakes of total and added sugars are high in the European countries considered, especially in children, and point to sweet products and beverages as the major contributors to added sugar intakes.